2020
DOI: 10.5380/rf.v50i2.62020
|View full text |Cite
|
Sign up to set email alerts
|

VIABILITY OF THE MINI-CUTTING TECHNIQUE IN THE PRODUCTION OF Drimys brasiliensis Miers SEEDLINGS

Abstract: Drimys brasiliensis, popularly known as cataia or casca-d'anta, is a tree species native to the Atlantic Forest and belonging to the family Winteraceae. Due to its seeds have dormancy due to embryonic immaturity, the present work aimed to evaluate the viability of the mini-cutting technique in D. brasiliensis in different seasons of collection of the propagules. Mini-cuttings from seedlings sprouts previously produced by conventional cutting were collected at six different times (December/2015, February/2016, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…low yield from trees, low germination rate, seed dormancy) is to apply micropropagation techniques, such as the ones presented in Barroso et al (2018). For instance, Maggioni et al (2020) showed that the mini-cutting technique is a viable option to Tab. 2 Model coefficients and adjusted coefficient of determination (R 2 ) of the linear models used to describe the seedling's root collar diameter, height, and survival in relation to different doses of controlled-release fertilizer (CRF) for the eight evaluated species.…”
Section: Discussionmentioning
confidence: 99%
“…low yield from trees, low germination rate, seed dormancy) is to apply micropropagation techniques, such as the ones presented in Barroso et al (2018). For instance, Maggioni et al (2020) showed that the mini-cutting technique is a viable option to Tab. 2 Model coefficients and adjusted coefficient of determination (R 2 ) of the linear models used to describe the seedling's root collar diameter, height, and survival in relation to different doses of controlled-release fertilizer (CRF) for the eight evaluated species.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal propagation by seminal minicuttings has been researched for several species of the Caatinga biome, such as Cedrela fissilis (XAVIER et al, 2003), Copaifera langsdorffii (DUTRA et al, 2014), Peltophorum dubium (MANTOVANI et al, 2017); Enterolobium contortisiliquum (FREITAS et al, 2018); Cabralea canjerana (BURIN et al, 2018), Hymenaea courbaril (MOURA et al, 2019); Drimys brasiliensis (MAGGIONI et al, 2020); Rubus sp. (JOAQUINI et al, 2021) and Myracrodruon urundeuva (LUZ et al, 2020;LEITE et al, 2021), in addition to the species Sarcomphalus joazeiro (SANTOS et al, 2021) object of this research.…”
Section: Introductionmentioning
confidence: 99%